Pengaruh Kinerja Perusahaan, Komite Audit, Pergantian Auditor Eksternal Terhadap Ketepatwaktuan Pelaporan Keuangan - Mardha Tillah; Nurzi Sebrina; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2019)
The purpose of this study is to know the effect of profitability, the influence of leverage, the influence of the number of internal audit committees, the influence of the independence of internal auditor committees, and the effect of external auditor changes on the timeliness of financial reporting of manufacturing companies listed on the Indonesia Stock Exchange 2013-2017. Finnancial statements as information will have benefits if delivered on time to the users for decision making. Financial statements are the final process in the accounting process that has an important role in measuring and evaluating the performance of a company. The analysis used is moderated regression analysis, moderated regression analysis (MRA). The results show that profitability has a significant positive effect, leverage does not have a significant effect, the number of audit committees has a positive effect, the independence of the audit committee has no significant effect and auditor turnover has no significant effect on the timeliness of financial statement submission.